1992
DOI: 10.1159/000126297
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Norepinephrine Mediated Corticotropin-Releasing Factor-41 Release from Cultured Fetal Hypothalamic Cells

Abstract: Catecholamines have been shown to activate hypothalamic corticotropin-releasing factor-41 (CRF) synthesis and release. In order to study the mechanisms involved, fetal hypothalamic cells were cultured and CRF release was measured by radioimmunoassay. Norepinephrine (NE) induced CRF release in a dose-dependent manner. Further studies were performed with a protein kinase C inhibitor, H-7(l-(5-isoquinolinesulfonyl)-2-methylpiperazine) and a protein kinase A inhibitor, IP-20. NE-stimulated CRF release was reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…These data also agree with those obtained from investigations of other in vitro systems [20,21,22,24], but not with those of Suda et al [25] who reported that NA inhibited CRH release from the hypothalamus in perifusion experiments. The present study also showed that CRH release increased both with increasing concentrations of NA for a fixed incubation time and increasing incubation times with a determined NA concentration.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These data also agree with those obtained from investigations of other in vitro systems [20,21,22,24], but not with those of Suda et al [25] who reported that NA inhibited CRH release from the hypothalamus in perifusion experiments. The present study also showed that CRH release increased both with increasing concentrations of NA for a fixed incubation time and increasing incubation times with a determined NA concentration.…”
Section: Discussionsupporting
confidence: 88%
“…We then studied the effect of nor adrenaline on short-term CRH release in cultured slices which has previously been reported as stimulatory in hypo thalamic explants [20] and in primary cultures of neonatal [21] or fetal [22] hypothalamic cells. Finally, we assessed the possible modulatory role of steroids on catecholamineinduced CRH release.…”
Section: Introductionmentioning
confidence: 99%
“…A recent microdialysis experiment (Tanaka et al, 1991) showed that the temporal profile of norepinephrine release from the amygdala of rats exposed to 20 min restraint stress closely matches that of CRF-IR described in the present work. In vitro norepinephrine evokes CRF-IR release from hypothalamic neurons (Tsagarakis et al, 1988;Hu et al, 1992), while microdialysis experiments show that CRF produces norepinephrine release from nerve terminals in prefrontal cortex and hypothalamus (Lavicky and Dunn, 1993), suggesting the existence of a reciprocal stimulating interaction between CRF and norepinephrine. Although the relevance of central norepinephrine in anxiety is still under debate, some of the behavioral effects produced by stress and ethanol withdrawal involve adrenoreceptor mediation (Berridge and Dunn, 1989;Glue et al, 1989;Soderpalm and Engel, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, 4-aminopyridine is known to release norepinephrine and acetylcholine in vitro (Drukarch et al, 1989;Heemskerk et al, 1990). Since norepinephrine or acetylcholine can produce CRF-IR release from the CNS neurons (Tsagarakis et al, 1988;Hu et al, 1992), it cannot be excluded that these or other neurotransmitters mediate the effects of 4-aminopyridine on CRF release within the amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…The suggestion that the central noradrenergic pathways might stimulate CRF biosynthesis in vivo is supported by the observations that insulin-induced hypoglycemia increases both the turnover of NE and the level of CRF mRNA expression in the hypothalamus (35,57). NE also stimulates the in vitro release and biosynthesis of CRF in fetal rat hypothalamic cells, and this effect involves the activation of both the A and C protein kinases and is mimicked by the phorbol ester TPA (58,59). TPA activates protein kinase C and increases the expression of the two major constituents of the AP-1 transcription factor complex, namely the protooncogene products Fos and Jun (60).…”
Section: Discussionmentioning
confidence: 99%